Stakeholder perceptions of scientific knowledge in policy processes: A Peruvian case-study of forestry policy development - Ramírez, L.F.; Belcher, B. (Oxford University Press, 2019)
There is a need to better understand how scientific knowledge is used in decision-making. This is especially true in the Global South where policy processes often occur under high political uncertainty and where a shift toward multilevel governance and decision-making brings new opportunities and challenges. This study applies knowledge-policy models to analyse a forestry research project that succeeded in influencing national policy-making. We investigate how decisions were made, what factors affected and shaped the policy process, and how scientific knowledge was used. The results highlight the complexity of policy processes and the related challenges in crossing the science-policy interface. Perceptions of scientific knowledge differed greatly among stakeholders, and those perceptions strongly influenced how scientific knowledge was valued and used. The findings suggest a need for researchers to better understand the problem context to help design and implement research that will more effectively inform decision-making.